Mechanical properties, water sorption characteristics, and compound release of grape seed extract-incorporated resins - Don Jeevanie EPASINGHE; Cynthia Kar Yung YIU; Michael Francis BURROW
Abstract Objective This study evaluated the effect of grape seed extract (GSE) incorporation on the mechanical properties, water sorption, solubility, and GSE release from the experimental adhesive resins. Material and Methods An experimental comonomer mixture, consisting of 40% Bis-GMA, 30% Bis MP, 28% HEMA, 0.26% camphorquinone and 1% EDMAB, was used to prepare four GSE-incorporated adhesive resins at concentrations of 0.5, 1, 1.5, and 2 wt%. The neat resin without GSE was used as the control. Six resin beams (25 mm x 2 mm x 2 mm) per group were prepared for flexural strength and modulus of elasticity evaluations using a universal testing machine at a crosshead speed of 1 mm/min. Five disks (6 mm in diameter and 2 mm in thickness) per group were used for microhardness measurements using a Leitz micro-hardness tester with Leica Qgo software. Five disks (7 mm in diameter and 2 mm in thickness) per group were prepared and stored in deionized water for 28 days. Water sorption, solubility, and GSE release in deionized water were calculated for each GSE-incorporated adhesive at the end of 28th day. Data was evaluated using one-way ANOVA and Tukey multiple comparisons. Results Flexural strength, modulus of elasticity and microhardness of GSE-incorporated adhesive decreased significantly with incorporation of 1.5% of GSE (p<0.05). Addition of GSE had no effect on the water sorption of the adhesive resins (p=0.33). The solubility of the resin also increased significantly with incorporation of 1.5% of GSE (p<0.05). Quantities of GSE release increased with increased concentration of GSE in the adhesive resin. Conclusion Up to 1% of GSE can be incorporated into a dental adhesive resin without interfering with the mechanical properties or solubility of the resins.